The past, history, and Corporate Social Responsibility - Phillips, Robert (Journal of business ethics, 2020)
An emerging body of research recognizes the importance of the past and history for corporate social responsibility (CSR) scholarship and practice. However, the meanings that scholars and practitioners can ascribe to the past and history differ fundamentally, posing challenges to the integration of history and CSR thinking. This essay reviews diverse approaches and proposes a broad conceptualization of the relationship between the past, history, and CSR. We suggest historical CSR as an umbrella term that comprises three distinct theoretical perspectives. The “past-of-CSR” perspective is concerned with the history of CSR and business ethics as a set of concepts and practices. The “past-in-CSR” perspective involves employing empirical historical research to substantiate and elaborate CSR concepts and theories. Finally, the “past-as-CSR” perspective seeks to understand the past as a living, yet contested, facet of current organizations, influencing contemporary perceptions of corporate and managerial responsibility. We then elaborate on conceptual issues and paths that may prove useful for future research. In all, this essay and the thematic symposium it precedes strive to deepen and broaden the salience of the past and history for thinking about business ethics and business responsibilities.